Pengembangan Modul Pembelajaran Sistem Reproduksi Terintegrasi Nilai-Nilai Islam Berbasis Problem Based Learning (PBL) di SMA/MA: Penelitian - Miftahul Shalsya Aulia Putri; Ardi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to develop a learning module on the reproductive system integrated with Islamic values based on the Problem Based Learning (PBL) model for Grade XI students (Phase F) at SMA Negeri 6 Solok Selatan. The study was motivated by findings that most students experienced difficulties in understanding the reproductive system material due to its abstract nature and the lack of interesting learning materials integrated with Islamic values. This research employed a Research and Development (R&D) method using the 4-D model modified into 3-D stages, namely define, design, and develop. Data were collected through teacher interviews, student observations, and validation and practicality tests conducted by lecturers, teachers, and students. The results showed that the developed learning module was valid and practical based on expert evaluation and user responses. The module effectively facilitated students to think critically, actively solve problems, and internalize moral and spiritual values in accordance with Islamic teachings through the integration of Qur’anic verses and hadiths relevant to the reproductive system topic. Therefore, this learning module is expected to serve as an effective alternative learning resource to enhance the quality of biology education in senior high schools.